Violence of young people over parents in Belgrade: Analysis of official data - Ljubičić Milana (Crimen (Beograd), 2019)
In this paper, we analyzed the violence of youth over parents. Parental victimization is the topic that is not enough revived in foreign, and especially not in domestic scientific literature. When it comes to our country, the focus of domestic researchers on two types of domestic violence is evident. Violence over women and children are considered to be the only relevant and highly troubling type of victimization by family violence. Our paper goals were to describe the characteristics of the perpetrators and victims, the characteristics of violence and family dynamics, and to try to understand the findings from the ecosystem's perspective. The ecosystem theory explains violence by the ontogenic, microsystem, mesosystem and egzosystem factors. We examined two dimensions of the model: ontogenetic, which emphasize individual characteristics, and microsystem - which is focused on factors connected with family system. We used documentary data on parents victimization gathered from the electronic database from Belgrade's Centers for Social Work for the period from 2010. to 2016. The sample consists of 85 files of fathers and mothers who were violated by their children, age 18-14. The data was collected and then statistically processed. The findings indicate that victims are mostly female, living in single-parent families, with poor educational, working and mental health status. It is also indicative that the share of fathers in the total number of victimized parents has a trend of growth. We noticed the differences in the structure of families from which parents come. Mothers mostly live alone with children, and fathers in a two-parent family. We find out that the predominant abusers are sons. The mental health of the perpetrators, regardless of gender, is fragile, and they are existencially dependent on their parents. Most of the parents are victimized by physical or physical and other forms of violence. The type of violence is significantly related to the sex of the abuser and the state of his mental health. Victimization is, as a rule, repeated and in a large number of cases, there is a danger of further progression of violence. Family dynamics is characterized by the absence of boundaries, rules, with parental permissiveness, and powerlessness. High dysfunctionality of family relations can be noted. In summary, the findings provide empirical confirmation of the ecosystem model assumptions.